Hubungan Kompetensi Sosial Guru Dengan Interaksi Edukatif Dalam Perspektif Peserta Didik - Amin, Amannasrullah (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2019)
Teachers as educators are required to have social competence. Therefore, teachers should be able to establish good communication with students, parents, neighbor, and co-worker's. In the meantime, educational interaction belief in good communication skills from teachers with students. However, no research has been done in person about the teachers social competence relationship with students educational interaction in the academic perspective. This study/research was meants to reveal: 1) How high are teachers sosial competence at SDIT Salsabila 3. 2) How strong are students educational interaction at SDIT Salsabila 3. 3) The teachers relationship with students educational interaction. And this is quantitative research. The research method used was the correlation study. The population is requested class SDIT Salsabila 3. The sampling technique used is sample. It's mean the entire population is sampled. The primary data collection uses an angket or questionnaire that has been validates by experts. Secondary data collection uses interviews, observations, and documentations.  Angular data calculated using parametric statistics to get the desired data,  and the prerequisite analysis was then performed using the Kolmogorof-Smirnov. After a prerequisite analysis was done, a hypothetical test was done using the product moment correlation technique. The study/research shows that the teachers social competence at SDIT Salsabila 3 the majority is the medium category. And the result of the students educational interaction of SDIT Salsabila 3 the majority in a sufficient/moderate category. This research shows a positive relationship between the teachers social competence to students educational interaction. Using a product moment testing technique helped with the SPSS 22.00 calculations program, has a coefficient correlation of 0,777. It's mean the link between the teachers social competence to students educational interaction is strong